Estimation Genetic Diversity by Using D2-Statistic in Maize Inbred lines (Zea mays L.) (Damascus University Journal of agriculture sciences, 2021)
A field experiment carried out at Abu Garash Farm, Faculty of Agriculture, Damascus University, during two consecutive growing seasons (2018 - 2019), in order to estimate the genetic diversity among five inbred lines of maize using D2 statistic based on some morphological, physiological and quantitative traits. The experiment was laid out according to randomized complete block design (RCBD) with three replications. Analysis of variance revealed highly significant differences among the evaluated inbred lines for all studied traits except for the anthesis-silking interval. The inbred lines were grouped into three different clusters. Cluster I contained three lines (IL-456-06, IL-90-14,    IL-200-14), whereas each of cluster II and cluster III contained one line only (IL-272-06), (IL-239-14) consecutively. The D2 analysis revealed that the maximum distance (205113376623004) was between the third and the first clusters. The maximum distance (89397527464328) was observed between the inbred lines IL-272-06 and IL-456-06, IL-90-14, indicating the existence of genetic variation between these lines and the possibility of using them to produce hybrids with high heterosis taking into account the investigated desirable traits.
Keywords: D2-Statistic; Genetic diversity; Genotypic variation; Maize